Operation mountain recovery - Davis, Justine (Davis, Justine. Cutter's code., 2020)
"After Deputy Brady Crenshaw rescues a confused woman from a near-fatal mountain accident, he's shocked at her confession. Even more bewildered when a determined dog urges him to shield her. Ashley admits she's afraid of powerful forces pursuing her. She may need more than protection. So as the lawman jeopardizes his career to hide her, Ashley starts to trust him and bond with the sly canine pushing them together. But exactly who is Ashley Jordan, really? And who wants to silence her?"--Back cover.